“Il pessimismo del mio libro”. Carl Einstein nel primo processo per blasfemia della Repubblica di Weimar* (Stato, Chiese e pluralismo confessionale, 2024)
"The pessimism of my book". Carl Einstein in the first blasphemy trial of the Weimar RepublicABSTRACT: The conviction for blasphemy imposed in 1922 on the writer Carl Einstein for the comedy Die schlimme Botschaft provides us with the opportunity of using the debate on crimes against religion to reflect on the epochal transition from the Wilhelminian Empire to the Weimar Republic. A picture emerges marked by strong contradictions, which manifest themselves also in violent street clashes and innumerable political murders, highlighting that the change of regime and the promulgation of the Constitution were not enough to overcome the profound resistance of a strongly conservative culture, still deeply rooted in the administration, judiciary and army leaders.SOMMARIO: 1. Un triste anniversario - 2. La blasfemia: un dibattito ‘ponte’ tra primo e secondo Reich - 3. Il riformismo di Kahl e la tregua tra classici e moderni - 4. Dall’abrogazionismo militante di Thümmel alla conservazione di Moser - 5. La vexata quaestio del bene giuridico - 6. L’insuccesso dei progetti di riforma - 7. La formazione critica di Einstein tra poetica e politica - 8. Primitivo, immediato, proletario - 9. Dalla rivolta alla rinuncia - 10. Sanguinosamente serio - 11. Rassegnazione e blasfemia: La cattiva novella - 12. Verso il processo - 13. Un procedimento ‘per sentito dire’ - 14. La parola all’imputato: “Dio ridotto in articoli” - 15. “Invecchiati troppo in fretta”